Transition-Metal-Catalyzed Annulative Coupling Cascade for the Synthesis of 3-Methyleneisoindolin-1-ones - Youn, So Won (Synthesis, 2020)
This short review describes the recent progress made on transition-metal-catalyzed annulative couplings for the synthesis of 3-methyleneisoindolin-1-ones, which are useful intermediates for the synthesis of numerous alkaloids and can be often found in a wide range of natural products and pharmaceuticals. In particular, new one-pot multiple C–C/C–N bond-forming processes for the construction of the 5-methylenepyrrol-2-one nucleus of such compounds are summarized.1 Introduction2 Intramolecular Cyclization Reactions: C3–N or C3–C3a and C–C Bond Formation3 Intermolecular Annulative Coupling Reactions3.1 C3–C3a and C3–N Bond Formation3.2 C1–C7a and C3–N Bond Formation3.3 C1–C7a and C1–N Bond Formation3.4 C1–C7a, C1–N and C3–N Bond Formation3.5 C3–C3a, C1–C7a, C1–N and C3–N Bond Formation: A Pd-Catalyzed One-Pot Sonogashira Coupling–Carbonylation–Amination–Cyclization Cascade4 Conclusion
Keywords: N-heterocycles; isoindolinones; transition-metal catalysis; C–H functionalization; cascade reactions; cyclizations; coupling reactions